Kajian Teknis dan Ekonomis Pembangkit Listrik Tenaga Mikrohidro (PLTMH)Di Desa Darul Makmur Kotamadya Subulussalam Provinsi Aceh - Pribadyo Pribadyo (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2016)
This study aims to review the magnitude of potential micro-hydro power ( MHP ) is technically and economically contained in Desa Darul Makmur Municipal Subulussalam used as a source of electrical energy using a propeller type turbine . Studies reviewed by the river flow and high water fall (head ) are available in the location using mathematical equations . The results of the study by considering topography , system micro-hydro power ( MHP ) with discharge parameters used by 0.07 m3 / sec and high water fall (head ) by 3.5 meters , micro-hydro power plants capable of resulting in a total energy 2,53 kW , with the price of electrical energy for Rp.805 / kWh and after distributed micro hydro power plants installed tenega can be used as illumination for 21 homes with power 0120 kW each house Keywords: PLTMH, potential energy, electric energy alternative